Consumer Response to Corporate Hypocrisy From the Perspective of Expectation Confirmation Theory - Zhigang, Wang; Lei, Zhang; Xintao, Liu (Frontiers in Psychology, 2020)
Based on the concept of hypocrisy perception, this paper studies and discusses consumers’ response to corporate social responsibility (CSR) hypocrisy perception, discusses the formation of consumers’ hypocrisy perception from the perspective of consumers’ expectation of CSR, and originally reveals the psychological and behavioral mechanisms of the generation of negative emotions and their role in consumer response. The results are as follows: (1) consumers’ CSR expectations and CSR perceived performance have a significant impact on their perception of hypocrisy; (2) consumers’ perception of hypocrisy has a significant impact on their negative emotions; (3) consumers’ negative emotions can have a significant impact on their attitudes and negative behaviors. The research results show that consumers’ expectations of CSR activities can affect consumers’ attitudes and behaviors, among which consumers’ perceived CSR performance, perceived hypocrisy, and negative emotions play an important role. In the implementation of CSR activities, enterprises should avoid making consumers have excessive expectations and appease their negative emotions, so as to improve the implementation effect of CSR activities.